AB0404 SARCOPENIA AND RELATED FACTORS AMONG PATIENTS WITH PRIMARY SJOGREN'S SYNDROME. (2nd June 2020) - Colak, S.; Tekgoz, E.; Hayme, S.; Sonaeren, İ.; Çinar, M.; Yilmaz, S.
Abstract : Background: Sarcopenia is the progressive and generalized loss of muscle mass, strength and function especially among elderly population. Inflammation may lead to sarcopenia regardless of age. Objectives: To evaluate the frequency of sarcopenia and related factors in patients with primary Sjogren's syndrome (SS). Methods: A total of 44 female patients with SS and 44 age matched female healthy controls were included in this cross-sectional study. Sarcopenia was evaluated by hand grip test, skeletal muscle index (SMI) and 6 meters gait speed (GS) test. According to recommendations of European Working Group on Sarcopenia in Older People (EWGSOP2) 2018, sarcopenia is defined as decrease in results of both hand grip test and SMI, whereas, probable sarcopenia is defined as only decrease in results of hand grip test. Mini Nutritional Assessment Short Form (MNA-SF) was used for evaluating nutritional statement. EULAR SS patient reported index (ESSPRI) and EULAR SS disease activity index (ESSDAI) used for evaluating disease activity. Patient global assessment (PGA) was assessed with visual analogue scale (VAS 0-10 cm). Patients with arthritis in dominant hand and/or ankle joints were excluded from the study. Results: The mean age of participants was 55.3±10.4 years. Eleven patients (25.0%) had probable sarcopenia in SS group and 2 (4.5%) in control group (p=0.007). Compared with healthy controls, SS patients had lower results of hand grip and 6 meters GS tests (p=0.005 and p<0.001, respectively). According to Mini Nutritional Assessment Short Form (MNA-SF), patients with probable sarcopenia had higher risk for malnutrition compared with patients with no sarcopenia (p=0.043). Patients with probable sarcopenia had higher scores of ESSPRI pain domain and patient visual analogue scale for global disease activity compared with patients with no sarcopenia (p=0.044 and p=0.036, respectively) (Table 1 ). In multivariate regression analysis ESSPRI pain was associated with hand grip strength (p=0.016, R 2 =0.13) and MNA was associated with SMI (p=0.005) (Table 2 ). Conclusion: Risk of sarcopenia is increased in patients with SS. In the current study, it is shown that pain is related with sarcopenia. ESPPRI pain is a sign of continuing chronic inflammation in patients with SS. Malnutrition, which can indirectly related with SS, may also contribute to this process. Excessive pain may lead to decrease daily activities and nutritional status of patients with SS. Evaluating pain and patient's global disease activity may help physicians to find out patients with increased risk for sarcopenia. Controlling disease activity and pain and preventing malnutrition may reduce the risk for development of sarcopenia. Acknowledgments: None to declare Disclosure of Interests: None declared